Current Concepts in Alignment in Total Knee Arthroplasty - Karasavvidis, Theofilos; Pagan Moldenhauer, Cale A.; Haddad, Fares S.; Hirschmann, Michael T.; Pagnano, Mark W.; Vigdorchik, Jonathan M. (The Journal of arthroplasty, 2023)
In an effort to increase satisfaction among total knee arthroplasty (TKA) patients, emphasis has been placed on implant positioning and limb alignment. Traditionally, the aim for TKA has been to achieve a neutral mechanical alignment (MA) to maximize implant longevity. However, with the recent spike in interest in individualized alignment techniques and with the advent of new technologies, surgeons are slowly evolving away from classical MA. This review elucidates the differences in alignment techniques for TKA, describes the concept of knee phenotypes, summarizes comparative studies between MA and individualized alignment, and provides a simple way to incorporate the latter into surgeons’ practice. In order to manage patients by applying these strategies in day-to-day practice, a basic understanding of the aforementioned concepts is essential. Transition to an individualized alignment technique should be done gradually with caution in a stepwise approach. Alignment and implant positioning are now at the heart of the debate and surgeons are investigating a more personalized approach to TKA.